2023
DOI: 10.1093/bmb/ldad023
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNAs in the management of human osteoporosis

Giuseppe Gargano,
Giovanni Asparago,
Filippo Spiezia
et al.

Abstract: Background Osteoporosis results in reduced bone mass and consequent bone fragility. Small interfering RNAs (siRNAs) can be used for therapeutic purposes, as molecular targets or as useful markers to test new therapies. Sources of data A systematic search of different databases to May 2023 was performed to define the role of siRNAs in osteoporosis therapy. Fourteen suitable studies were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Therefore, we conclude that circ_0076684 contributes to OS progression through its regulatory effect on CUX1 expression, highlighting a novel aspect of CUX1's multifaceted role in cancer biology. Given the potential application of RNA interference technology in human diseases in recent years [ 25 27 ], targeting circ_0076684, CUX1, and RUNX2 may have potential application value in the treatment of OS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conclude that circ_0076684 contributes to OS progression through its regulatory effect on CUX1 expression, highlighting a novel aspect of CUX1's multifaceted role in cancer biology. Given the potential application of RNA interference technology in human diseases in recent years [ 25 27 ], targeting circ_0076684, CUX1, and RUNX2 may have potential application value in the treatment of OS.…”
Section: Discussionmentioning
confidence: 99%
“…And circ_0044235 could regulate PIK3R3 through miR-375. Recently, siRNAs have been found to regulate tendon homeostasis, osteoporosis and arthritis progression [ 33 35 ]. Here, we found that PIK3R3 silencing abolished the role of anti-miR-375 on OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA and siRNAs have been confirmed to play vital function in human diseases [ 23 27 ]. According to reported studies, circ_0000376 might be involved in regulating OS development through sponging miR-432-5p [ 17 ].…”
Section: Discussionmentioning
confidence: 99%